IMPLEMENTATION OF CONCOLIC UNIT TESTING IN TESTING BINARY SEARCH ALGORITHM USING JCUTE - Feta, Neneng Rachmalia; Fitria, Fitria (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2022)
Testing is a process of implementing a program with the aim of finding an error. A good test case is one of the tests that have the possibility of finding an undisclosed error. One of the existing types of testing is the Concolic Unit Testing Engine. In this research, testing is applied using the Jcute tool, which is a tool to systematically and automatically test sequential C programs (including instructions) and Java programs together. This test is carried out on the search function of an element of data in the Binary Search Search Algorithm. However, to check whether concolic testing can detect bugs in the software practically through case studies. This research describes a case study of the application of a test tool to a Java application. Through this research, we tested the path coverage and Branches Covered. We can also find out the details of total branches covered; total functions invoked, percentage of branches covered and the number of iterations. JCUTE can also find an interleaving of two sequences or circuits that results in an infinite loop.